Financial literacy and new business entry - Tomasz Skica; Juraj Mikuš; Marian Holienka (Financial Internet Quarterly, 2022)
The issue of the relationship between financial literacy and entrepreneurship is still not a fully explored research area. On the one hand, there are common views that financial literacy and education in finance are necessary in every individual's life, and that an insufficient level of finan- cial literacy may result in erroneous economic decisions. On the other hand, research on the impact of narrowly defined financial literacy on business start-up decisions is still rare. As a re- sult, there are no clear indications regarding the need for education in the area of finance in or- der to stimulate entrepreneurial decisions, including the survival of launched economic under- takings. This article deals with the relationship between financial literacy and chosen entrepre- neurial aspects such as 1) Phases of Entrepreneurial Activity; 2) Entrepreneurial potential; 3) Mo- tivation; 4) Involvement in the technology sector; and 5) Business exit reasons. All of the above aspects are embedded in the context of financial literacy. The article sheds light on the relation- ship between financial literacy and entrepreneurship and creates a background for further attempts to deepen understanding of this issue.
Keywords: L26; G53; J24; 330; financial literacy; business entry; entrepreneurship